ANALISIS PENGARUH PERDAGANGAN INTERNASIONAL DAN VARIABEL MAKRO EKONOMI TERHADAP PERTUMBUHAN EKONOMI INDONESIA - Mikhral Rinaldi; Abd Jamal; Chenny Seftarita (Jurnal Ekonomi dan Kebijakan Publik Indonesia, 2017)
This study aimed to analyze the effect of international trade variable that consists of the current account, exchange rates and macroeconomic variables consisting of investment and employment to economic growth of Indonesia. This study uses data period 2000 to 2015. The model used is Ordinary Least Square (OLS) by using software Eviews 7. The results showed that the variables of labor and significant positive effect on economic growth in Indonesia, when labor has increased as much as 10,000 GDP will rise by 47.2 Rupiah. Variable current account significant negative effect on the GDP of Indonesia, when the current account increased by US $ 1 million Indonesia GDP will be decreased by 9.77 Rupiah. Variable rate and a significant negative effect on the GDP of Indonesia, when Rupian depreciated by 1 Indonesian Rupiah GDP will be decreased by 76.5 Rupiah. In this study the variable investment does not Affect the GDP of Indonesia.